2017
DOI: 10.1002/em.22122
|View full text |Cite
|
Sign up to set email alerts
|

In vivo pig‐a and micronucleus study of the prototypical aneugen vinblastine sulfate

Abstract: The Pig-a assay is being used in regulatory studies to evaluate the potential of agents to induce somatic cell gene mutations and an OECD test guideline is under development. A working group involved with establishing the guideline recently noted that representative aneugenic agents had not been evaluated, and to help fill this data gap Pig-a mutant phenotype and micronucleated reticulocyte frequencies were measured in an integrated study design to assess the mutagenic and cytogenetic damage responses to vinbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Since then, further studies have been performed on specific aspects of these methods addressing the issues identified at the 6th IWGTP (e.g. Itoh et al, 2015;Shimada et al, 2015;Shigano et al, 2016;Avlasevich et al, 2018;Hori et al, 2019;Itoh and Hattori, 2019).…”
Section: A3 Micronucleus Assay Techniques In Tissues Other Than Bone ...mentioning
confidence: 99%
“…Since then, further studies have been performed on specific aspects of these methods addressing the issues identified at the 6th IWGTP (e.g. Itoh et al, 2015;Shimada et al, 2015;Shigano et al, 2016;Avlasevich et al, 2018;Hori et al, 2019;Itoh and Hattori, 2019).…”
Section: A3 Micronucleus Assay Techniques In Tissues Other Than Bone ...mentioning
confidence: 99%
“…For the Pig‐a assay, statistical analyses were performed on the mutant cell frequencies CD59‐negative RBC and CD59‐negative RET per 10 6 and RET percent (%RET) as described in Avlasevich et al (Avlasevich et al ., 2018). Accordingly, CD59‐negative RBC and CD59‐negative RET per 10 6 frequencies were log(10) transformed with a 0.1 offset added to each frequency prior to log transformation.…”
Section: Methodsmentioning
confidence: 99%